Method of Internalizing the Values of Moral Education of Pesma KH Mas Mansyur Student - Muhammad, Awwaluddin Annashir; Latifatul Inayati, Nurul (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
The development of science and technology has many negative impacts. The most dangerous impact is moral damage. Currently, pesantren is one of the choices of the community in improving morals through Islamic and religious learning. This study aims to identify the implementation of the internalization of moral education values and the obstacles to the internalization of moral education values at Pondok Pesma KH Mas Mansyur. This research is qualitative with data collection methods of observation, documentation, interviews. The data analysis technique starts from data collection as well as data reduction, data presentation, verification and conclusions. The results of the research on the process of internalizing moral education carried out on Pesma students through moral habituation towards themselves by instilling honesty, trustworthiness, patience, tawadhu, doing good (ihsan). in daily habits and building good interactions. The method of internalizing the value of moral education in Pesma is the training method, habituation method, exemplary method, advice method, independence method. The implementation of moral education in Pesma KH mas Mansyur is carried out by example, learning process, and association. The supporting factor is the support and positive encouragement from parents, friends and the board of care. While inhibiting factors include coming from oneself, such as students often going home every weekend. Mahasantri return from campus activities late at night. This causes activities at pesma to be missed. In addition, the bad habit of being lazy at home that is carried over to the pesantren makes it less than optimal in carrying out activities in the student pesantren well.